Sibling Health, Schooling and Longer-Term Developmental Outcomes - Chris Ryan; Anna Zhu (Institute for the Study of Labor (IZA), 2016)
We explore the extent to which starting primary school earlier by up to one year can help shield children from the detrimental, long-term developmental consequences of having an ill or disabled sibling. Using data from the Longitudinal Study of Australian Children, we employ a Regression Discontinuity Design based on birthday eligibility cut-offs. We find that Australian children who have a sibling in poor health persistently lag behind other children in their cognitive development - but only for the children who start school later. In contrast, for the children who commence school earlier, we do not find any cognitive developmental gaps. The results are strongest when the ill-health in the sibling is of a temporary rather than longer-term nature. We hypothesise that an early school start achieves this by lessening the importance of resource-access inequalities within the family home. However, we find mixed impacts on the gaps in non-cognitive development.
Keywords: J13; I21; 330; educational economics; human capital; school starting age; sibling health